Extract Date Juice and Healthy Date Milk - Aditya Wulung; Prakoso Arifin (Asian Journal of Social and Humanities, 2023)
The entrepreneurial potential of date juice and date milk in Indonesia is very large, because there are so many benefits for the health of the body and the word dates are synonymous with Islam, Indonesia has a Muslim majority population. This entrepreneurial project also wants to explain how healthy the content of date palm juice is. Drinking date juice every day is very good, which will provide nutrition throughout the day. The benefits of dates, as raw materials for date juice and date milk for body health are numerous, namely (Source: USDA National Nutrient Data Base) supporting bone health and strength, overcoming intestinal disorders, helping to treat anemia, tackling allergies, assisting in the recovery process for dengue fever, energy booster, maintaining a healthy nervous system, improving memory and brain work systems, preventing insomnia, maintaining heart health, controlling diarrhea, preventing stomach cancer, source of antioxidants, prevent blood clots. The aim of this entrepreneurial project is to present and introduce and make the culture of drinking healthy drinks, namely date milk or date juice, a daily drink. The choice of date milk and date juice products apart from the many benefits, the products have the advantage of being ready to drink both date milk and date juice which are still fresh.